y-11=x(x-8)

Simple and best practice solution for y-11=x(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-11=x(x-8) equation:


Simplifying
y + -11 = x(x + -8)

Reorder the terms:
-11 + y = x(x + -8)

Reorder the terms:
-11 + y = x(-8 + x)
-11 + y = (-8 * x + x * x)
-11 + y = (-8x + x2)

Solving
-11 + y = -8x + x2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + y = -8x + 11 + x2

Combine like terms: -11 + 11 = 0
0 + y = -8x + 11 + x2
y = -8x + 11 + x2

Reorder the terms:
y = 11 + -8x + x2

Simplifying
y = 11 + -8x + x2

See similar equations:

| 11+x=6(5x-3) | | 132+77t= | | -w^6+4w^4-4w^2+1=3.981 | | 60-24x= | | -3-3n=-3(2n-5) | | -15=r/5 | | -3z=8-3z | | 24x+64= | | Y=-4x^2+16x+20 | | 3a^3+3ab^2+2a^2b+2b^3= | | -(5-2)=5+2 | | 5x/8-3x/8 | | x*x-2x=3x+108 | | 5/6(-3/4) | | -42+-54= | | Y=-4x^2+16+20 | | 2x^4-x^3-6x^2=0 | | 4z+3z+6=90 | | 100-50d= | | x/y-1/5 | | x^2-2(x-1)=x^2(x-1) | | 6x+16-5x=-3-12 | | 7x/10-9=x/5+11 | | 3x+1=-4x-6x | | t/6=-10 | | -3(12+r)=-72 | | 42r-18= | | 2l*2w=300 | | 7x-5(3x+12)= | | 3(11r-13)= | | -3(12+2)=-72 | | 8+1w=3+2w |

Equations solver categories